CREATININE CLEARANCE AS EFFECTIVE NON-INVASIVE MARKER IN DETERMINING GASTROINTESTINAL LESIONS AND HELICOBACTER PYLORI INFECTION: Non-Invasive Marker in Helicobacter Pylori Infection - Jamil, Zubia; Ambreen, Saima; Ahsan, Omar (Pakistan Armed Forces Medical Journal, 2018)
Objective: The objective of this study focuses to unfold the importance of creatinine clearance in determining the gastrointestinal mani-festations and Helicobacter Pylori infection. Study Design: Cross-sectional comparative study. Place and Duration of Study: Medicine department of Fauji Foundation Hospital Rawalpindi, from Jun 2015 to Dec 2016. Material and Methods: Creatinine clearance of 73 CKD patients was calculated. UGI endoscopy was performed to detect gastro-intestinal lesions. H.pylori was detected by histopathology of gastric mucosal biopsy. The diagnostic accuracy of CCl in determining the presence of gastrointestinal (GI) lesions was determined by receiver operating characteristic (ROC) curve (AUC). Cut-off value, sensitivity, specificity, positive and negative predictive values, positive and negative likelihood ratios were obtained by Youden index. Results: Mean CCl was 27.09 ± 12.16 ml/min. Diabetes mellitus was the top most cause of CKD (45.2%). Upper GI endoscopic lesions were present in 68.5% patients (p-value<0.05). The most common abnormality was erythematous gastritis. H. pylori infection was lower in disease group compared to controls, but statistically insignificant (p>0.05). The AUC for CCl in determining the gastrointestinal lesions was 0.8 (p-value≤0.0001), cutoff value was <35ml/min (Sensitivity 81.82%, Specificity 72.4%). The AUC for CCl in determining the presence of H. Pylori infection was 0.7 (p-value=0.0004), cutoff value was <27 ml/min (Sensitivity 83.33%, Specificity 58.18%). Conclusion: CCl was found, noninvasive marker in predicting the GI abnormalities. It can be used to identify the high risk patients. Such patients then can undergo endoscopy for further management. H.pylori eradication therapy should be offered to those patients in whom its presence is proven by other tests as well.